HUBUNGAN PENGETAHUAN RESPONDEN DAN FAKTOR DEMOGRAFI DENGAN PERNIKAHAN USIA DINI DI KECAMATAN BANYUMANIK TAHUN 2016 - Delita Septialti; Atik Mawarni; Djoko Nugroho; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Early marriage is a marriage performed before 20 years. Early marriage to be related with health reproduction and demography. In 2006 there were 22% early marriage in Banyumanik Subdistric, Pudakpayung (27%), Banyumanik (16%), Jabungan (9%), Tinjomoyo (9%) was the villages with highest number of early marriage. The purpose of this study was to analyze relationship beetwen knowledges and demography factors with early marriage in Banyumanik subdistric. This research used explanatory research with cross-sectional study design. Sample in this study were 119woman who perfom her marriages in the period of 2016. The sample was selected by proporsional random sampling. Data analyzed with univariat, bivariate with chi square test, multivariate with logistic regression, and significance level α= 5%. The results showed that respondents with low education (46.2%), less sexual behavior in dating (48,7%), the income of parents low from UMR (61,3%), less knowledges (58%), and (33%) early marriage incident. There are relation of knowledge respondents (p value=0.043), the income of parents (pvalue=0.001) but there is no relation of sexual behavior in dating (p value=0.078) and educational respondent (p value=0.173) with early marriage incident. Have an both relation between knowledge and family impact with early maariage. for girls suggest to increase their knowledges obout health reproduction and family planning in promotion from primary health center. In each activity such us promotion, simulation, and interpersonal communication.